Analysis of the Effects of Economic Growth, Minimum Wages, and Education on Unemployment in Indonesia During the 2014-2023 Period - Habibie, Muhammad Fadhlan; Suman, Agus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to analyze the impact of economic growth, minimum wage, and education on unemployment in Indonesia during the 2014-2023 period. The study is motivated by the high unemployment rate in Indonesia during the Jokowi administration compared to the SBY administration. The data used is secondary data from the Badan Pusat Statistik (BPS), covering 34 provinces in Indonesia. The analysis method employed is multiple linear regression with panel data. The results show that economic growth and minimum wage have a significant negative effect on the unemployment rate, while education does not have a significant effect on unemployment. Simultaneously, economic growth, minimum wage, and education significantly influence the reduction of unemployment. These findings suggest the importance of improvements in the economic sector, the implementation of minimum wage policies, and the quality of education in reducing unemployment in Indonesia. The implications of this study can assist the government and other stakeholders in formulating effective policies to alleviate unemployment in the region.